PENETRATION OF ISLAMIC FINTECH MODEL IN PROMOTING THE ACCELERATION OF MSMES IN THE EASTERN COASTAL OF ACEH - Dhian Rosalina; Meutia Dewi; Saparuddim Siregar; Sugianto Sugianto (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to find ways to introduce Islamic fintech that fit the social, cultural, and economic needs of SMEs in Aceh’s eastern coastal area. The main goal is to support financial and digital inclusion and improve literacy. This research is important because coastal SMEs rarely use Islamic fintech. The main reasons are limited internet access, weak digital infrastructure, and low worker readiness, even though Aceh’s strong religious culture supports Islamic financial products.This research uses both exploratory and descriptive methods. It brings together secondary data from Otoritas Jasa Keuangan and Badan Pusat Statistik reports, along with academic literature, and primary data from interviews and questionnaires. Key informants include people from Bank Syariah Indonesia, Bank Aceh, coastal salted fish SMEs, local government agencies, and Islamic fintech service providers. The data were analyzed using an interactive model, then reviewed using a SWOT analysis.The results show that Islamic fintech can improve access to financial services and help coastal SMEs grow. However, its use is still limited by poor digital access and low financial and digital literacy. The SWOT analysis points to a model with three main pillars: improving digital access, increasing SME literacy and mentoring, and strengthening regulatory cooperation and the Islamic financial ecosystem. These steps are meant to make Islamic fintech more relevant and sustainable for local SMEs.